Activator protein‐1 mediated CYP6ER1 overexpression in the clothianidin resistance of Nilaparvata lugens (Stål). Issue 10 (2nd June 2021) - Jin, Ruoheng; Wang, Yue; He, Biyan; Zhang, Yunhua; Cai, Tingwei; Wan, Hu; Jin, Byung Rae; Li, Jianhong
Abstract: BACKGROUND: Nilaparvata lugens, a destructive rice pest in Asia, has developed resistance to many insecticides, including the neonicotinoid clothianidin. CYP6ER1 plays an important role in N. lugens resistant to clothianidin, but only limited information on the transcriptional regulation of CYP6ER1 overexpression in clothianidin resistance is available. RESULTS: In this study, the transcription factor activator protein 1 ( AP‐1 ) was found to be overexpressed in a clothianidin‐resistant strain of N. lugens and several field resistant populations. RNA interference‐mediated silencing of NlAP‐1 significantly decreased CYP6ER1 expression and increased the susceptibility of N. lugens to clothianidin. Additionally, NlAP‐1 was highly expressed in egg and adult stages, and in midguts, and NlAP‐1 was upregulated and induced to a greater extent in the clothianidin‐resistant strain after exposure to clothianidin. Finally, dual‐luciferase reporter assays confirmed the interaction between NlAP‐1 and the two predicted binding sites in the CYP6ER1 promoter. CONCLUSION: NlAP‐1 bound the −1388 to −1208‐bp region of the CYP6ER1 promoter, enhancing its activity and then regulate the expression of CYP6ER1 . These findings enhance our knowledge of the transcriptional regulation of the P450 genes that mediate insecticide resistance in insect pests. © 2021 Society of Chemical Industry. Abstract : Activator protein 1 was upregulated in clothianidin‐resistant N. lugens . NlAP‐1 knockdown increased susceptibility of N. lugens to clothianidin. NlAP‐1 bound the −1388 to −1208‐bp region of the CYP6ER1 promoter, enhancing its activity.